Deep intronic 'mutations' cause hemophilia A: application of next generation sequencing in patients without detectable mutation in F8 cDNA. (12th September 2013) - Pezeshkpoor, B.; Zimmer, N.; Marquardt, N.; Nanda, I.; Haaf, T.; Budde, U.; Oldenburg, J.; El‐Maarri, O.
Summary Background In a small group of typical hemophilia A (HA) patients no mutations in the F8 coding sequence (cDNA) could be found. In the current study, we performed a systematic screening of genetic and non‐genetic parameters associated with reduced FVIII:C levels in a group of mostly mild HA (only one moderate) patients with no detectable mutations in F8 cDNA. Methods We determined FVIII and VWF activity and antigen levels and performed VWF‐FVIII binding (VWF:FVIIIB) and VWF‐collagen binding assays (VWF:CB) as well as VWF multimer analysis. VWF was completely sequenced to exclude mutations. The F8 locus, including the introns, was sequenced using overlapping long‐range PCRs (LR‐PCRs) combined with a next generation sequencing (NGS) approach. Moreover, the F8 mRNA was analyzed quantitatively and qualitatively by real‐time PCR (qRT) and overlapping reverse transcription (RT) PCRs, respectively. Results All VWF tests were normal. The LR‐PCRs demonstrated the integrity of the F8 locus. Eight unique polymorphisms were found in the patients, with two being recurrent. Furthermore, RT‐PCRs analysis confirmed that two of the unique variants create detectable new cryptic splice sites in the patients that result in the introduction of intronic DNA sequences into the mRNA and create premature stop codons. Conclusion By systematically excluding all possible causes of HA, we could with great certainty conclude that deep intronic mutations in F8, although rare, cause abnormal mRNA splicing, leading to mild HA.